A new perspective of particle adsorption: Dispersed oil and granular materials interactions in simulated coastal environment. Issue 1 (15th September 2017) - Meng, Long; Bao, Mutai; Sun, Peiyan
Abstract: This study, adsorption behaviors of dispersed oil in seawaters by granular materials were explored in simulation environment. We quantitatively demonstrated the dispersed oil adsorbed by granular materials were both dissolved petroleum hydrocarbons (DPHs) and oil droplets. Furthermore, DPHs were accounted for 42.5%, 63.4%, and 85.2% (35.5% was emulsion adsorption) in the adsorption of dispersed oil by coastal rocks, sediments, and bacterial strain particles respectively. Effects of controlling parameters, such as temperature, particle size and concentration on adsorption of petroleum hydrocarbons were described in detail. Most strikingly, adsorption concentration was followed a decreasing order of bacterial strain (0.5–2 μm) > sediments (0.005–0.625 mm) > coastal rocks (0.2–1 cm). With particle concentration or temperature increased, adsorption concentration increased for coastal rocks particle but decreased for sediments particle. Besides, particle adsorption rate of petroleum hydrocarbons ( n -alkanes and PAHs) was different among granular materials during 60 days. Graphical abstract: Highlights: We quantitatively demonstrated both DPHs and oil droplets were absorbed by granular materials. We confirmed the adsorption ratios of DPHs and oil droplets about three particles. Maximum adsorption was bacterial strain particle when compared with another two particles. Particle concentrations and temperature could affect adsorption of three particles. Particle adsorption rate of petroleum hydrocarbons were different from three particles.